2020
DOI: 10.1108/et-04-2020-0075
|View full text |Cite
|
Sign up to set email alerts
|

Standing at the crossroads: the vulnerabilities of Australian business schools

Abstract: PurposeTo identify key factors that are contributing to vulnerability in business schools in Australian public universities and determine the degree of vulnerability exhibited by these schools.Design/methodology/approachUsing a multi-criteria assessment (MCA) approach, a framework is developed to determine which business schools are most vulnerable to disruptions and uncertainty.FindingsThe findings show a lack of preparedness on the part of many business schools, particularly those relying heavily on internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…While Thailand is clearly well served by many tertiary education providers, it falls short regarding internationally recognised quality (Nagi, 2018). Although university rankings are contentious (Hogan et al, 2020), there is an overall downward trend in the international ranking of Thai universities (Nagi, 2018). If we exclude the Asian Institute of Technology (not classified by MHESRI as a Thai HEI), only five public HEIs (Chulalongkorn, Thammasat, Mahidol, Chiang Mai, and Kasetsart) have a position in the QS Rankings of business management studies (QS, 2022).…”
Section: Thai Institutional Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…While Thailand is clearly well served by many tertiary education providers, it falls short regarding internationally recognised quality (Nagi, 2018). Although university rankings are contentious (Hogan et al, 2020), there is an overall downward trend in the international ranking of Thai universities (Nagi, 2018). If we exclude the Asian Institute of Technology (not classified by MHESRI as a Thai HEI), only five public HEIs (Chulalongkorn, Thammasat, Mahidol, Chiang Mai, and Kasetsart) have a position in the QS Rankings of business management studies (QS, 2022).…”
Section: Thai Institutional Contextmentioning
confidence: 99%
“…Most of the attention has been paid to business schools in Western countries, where public universities have had to face the challenge of affirming their legitimacy in an increasingly crowded tertiary education market (Hogan et al, 2020), where 'hyper-competition' exists (AASCB International, 2017). For example, Hogan et al (2021), responding to the discourse above about what business schools in public universities should offer, sought to determine how business schools in Australian public universities claimed to create public value.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, what is to become of some Australian public university-based business schools? Hogan et al (2020) have shown that some second-tier and regional institutions are highly vulnerable to market forces. Susceptibility to continued external threats is particularly pertinent if a more diverse range of registered providers can facilitate accredited business and management training.…”
Section: Lessons For Decision Makersmentioning
confidence: 99%
“…Recent articles by Hogan et al (2020, 2021a, b) on the state of higher education in Australia assisted with identifying the most critical literature. However, the net was cast wider to capture a complete array of insights.…”
Section: Background and Literaturementioning
confidence: 99%
See 1 more Smart Citation